Toward A Wireless Contact Lens Sensor System with a Micro-Capacitor for Intraocular Pressure Monitoring on in-vitro Porcine Eye - Yeh, Guan-Ting; Wu, Tsung-Wei; Tsai, Shang-Wei; Hsu, Shun-Hsi; Chiou, Jin-Chern (My University, 2015)
This work presents a type of capacitive sensor for intraocular pressure (IOP) measurement on soft contact lens with Radio Frequency Identification (RFID) module. The flexible capacitive IOP sensor and Rx antenna was designed and fabricated using MEMS fabrication technologies that can be embedded on a soft contact lens. The IOP sensing unit is a sandwich structure composed of parylene C as the substrate and the insulating layer, gold as the top and bottom electrodes of the capacitor, and Hydroxyethylmethacrylate (HEMA) as dielectric material between top plate and bottom plate. The main sensing principle is using wireless IOP contact lenses sensor (CLS) system placed on corneal to detect the corneal deformation caused due to the variations of IOP. The variations of intraocular pressure will be transformed into capacitance change and this change will be transmitted to RFID system and recorded as continuous IOP monitoring. The measurement on in-vitro porcine eyes show the pressure reproducibility and a sensitivity of 0.02 pF/4.5 mmHg
Keywords: Contact lens system; Intraocular pressure; Capacitor sensor; Non-invasive Biomedical Monitoring System